2023
DOI: 10.1093/molbev/msad093
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Adaptation to Leaf and Root Bacterial Microbiota inArabidopsis thaliana

Abstract: Understanding the role of the host genome in modulating microbiota variation is a need to shed light on the holobiont theory and overcome the current limits on the description of host-microbiota interactions at the genomic and molecular levels. However, the host genetic architecture structuring microbiota is only partly described in plants. In addition, most association genetic studies on microbiota are often carried out outside the native habitats where the host evolves and the identification of signatures of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…Local adaptation is mediated by many features of the environment, because selection in natural habitats is usually driven by a set of interacting factors, including abiotic and biotic ones 28,43 . Nevertheless, the traditional research focus in local adaptation has been on abiotic factors such as climate, or mixed abiotic-biotic factors such as soil 29 , even though biotic factors such as herbivores, pollinators, microbiota, or competitors are equally or sometimes even more important than abiotic factors for plant survival and reproduction 28,4447 . How quickly organisms adapt to the multivariate local habitat conditions 15,35 , and which genomic changes enable such adaptation 17 is not well known, despite the importance of rapid adaptation to the survival of many organisms in the face of regional- and global change.…”
Section: Discussionmentioning
confidence: 99%
“…Local adaptation is mediated by many features of the environment, because selection in natural habitats is usually driven by a set of interacting factors, including abiotic and biotic ones 28,43 . Nevertheless, the traditional research focus in local adaptation has been on abiotic factors such as climate, or mixed abiotic-biotic factors such as soil 29 , even though biotic factors such as herbivores, pollinators, microbiota, or competitors are equally or sometimes even more important than abiotic factors for plant survival and reproduction 28,4447 . How quickly organisms adapt to the multivariate local habitat conditions 15,35 , and which genomic changes enable such adaptation 17 is not well known, despite the importance of rapid adaptation to the survival of many organisms in the face of regional- and global change.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of holobionts in their native habitats are still underrepresented. To our knowledge, Roux et al, 2023 is the only large plant in situ survey describing a highly variable genetic architecture between plant compartments (leaves and roots) and seasons (fall and spring) for the bacterial A. thaliana microbiome (12). As mentioned by the authors, the next step is to compare fungal and bacterial microbiomes in situ to identify common plant genetic loci structuring inter-kingdom interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies showed the power of GEA to identify plant loci associated with biotic communities. This has been demonstrated both in the non-model plant species B. incana and its associated pollinator communities (10), and in the model plant species Arabidopsis thaliana and its plant-plant (11) and plant-microbiome (12) interactions. The latter study is the only describing adaptive loci associated with bacterial descriptors in natural plant populations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The impact of the microbiome on plant health, particularly in the context of Arabidopsis thaliana , a model organism for plant biology, has been extensively studied and reveals complex interactions [ 174 , 175 , 176 , 177 ]. These studies have shown that healthy plants host diverse and structured communities of microorganisms that colonize almost every part of the plant [ 177 , 178 , 179 ]. This plant-associated microbiome offers significant advantages to the host, including promoting growth, aiding in nutrient uptake, enhancing stress tolerance, and providing resistance to pathogens [ 180 ].…”
Section: Advances In Microbiome Research and Omics Technologiesmentioning
confidence: 99%